Counter-selection markers for allele replacement in Burkholderia pseudomallei - López Peláez, Carolina María, author; Schweizer, Herbert P., advisor (Colorado State University. Libraries, 2008)
Burkholderia pseudomallei is a gram negative bacillus that lives in the soil of tropical regions around the planet and causes melioidosis in humans, a disease endemic in regions of Southeast Asia and Northern Australia. The United States government has classified B. pseudomallei, and its relative Burkholderia mallei, as potential bioterrorism agents. The increased interest in these complex pathogens initiated a quest to better understand the biology of these bacteria at the molecular level. Completed genome sequences of diverse strains have provided a wealth of information that opened new venues for further study. Many genetic tools have been successfully adapted for use in Burkholderia species, but others are yet to be discovered. The ability to introduce unmarked single nucleotide changes or other genetic modifications into the B. pseudomallei genome, by way of the host's natural homologous recombination pathways, has been hampered by the lack of a suitable counter-selection marker that works efficiently in different wild-type strains. Counter-selection markers allow for the positive selection of strains that have lost the marker and other unwanted sequences around them. This dissertation describes the search for a system that allows isolation of unmarked mutations and single nucleotide changes in the B. pseudomallei genome. Two different systems were proven effective and provide alternative options for isolation of allelic mutants of genes of interest. The first method uses a mutated allele of the B. pseudomallei pheS gene. This gene encodes for a subunit of phenylalanine tRNA synthase. A specific PheS mutant protein exhibits relaxed substrate specificity, allowing for incorporation of a toxic chlorinated phenylalanine analog into proteins resulting in death of cells expressing the mutant protein. Counter-selection based on the mutant pheS gene of B. pseudomallei allowed for the creation of amrRAB-oprA deletion mutants of different B. pseudomallei strains. The AmrAB-OprA efflux pump is responsible for intrinsic resistance to aminoglycosides and macrolides in B. pseudomallei. Consequently, efflux pump mutants became sensitive to selected aminoglycosides. Also, as a proof of concept experiment, a clean unmarked purM mutant was created. purM mutants are thiamine and adenine auxotrophs and have been shown to result in a strong attenuation of virulence in a mouse model of melioidosis. A second system based on the I-SceI homing endonuclease of Saccharomyces cerevisiae was also developed. Expression of the endonuclease in cells containing chromosomal I-SceI recognition sites integrated in their chromosomes in place of counter-selection markers via homologous recombination, leads to the selection of isolates that have lost the sites and thus unwanted sequences containing them. This is because I-SceI creates double-strand breaks and promotes recombination between nearby homologous sequences. As a proof of concept experiment this system was also used to create a B. pseudomallei purM mutant. Furthermore, by creating a temperature sensitive fabD mutant due to a point mutation in the fabD gene proved that I-SceI could be used to create point mutations. FabD is an essential enzyme of the bacterial fatty acid biosynthesis pathway. In summary, this report describes the first counter-selection markers that work in wild-type B. pseudomallei strains. Availability of the markers will allow the routine generation of mutants required for studies of the biology and pathogenesis of this understudied pathogen and the related B. mallei.
Keywords: Burkholderia pseudomallei; counter-selection; I-SceI; melioidosis; mutagenesis; pheS; molecular biology; microbiology